Review of cesarean section medical record document at RSIA Srikandi IBI Jember - Nurmawati, Ida; Rachmawati, Desy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Cesarean section is a type of abnormal labor that gives birth to a fetus live through the abdomen with obstetric surgery. The incidence of cesarean section at RSIA Srikandi IBI Jember has increased from 2015 to 2017, whereas in 2018 it decreased. Still, the prevalence tends to be the same as the incidence of cesarean section in 2017. The percentage of the cesarean section from 2015 to 2018 was 59.6%, 63%, 65.2% and 60%. Purpose: to analyze the determinants of the cesarean section at RSIA Srikandi IBI Jember. This study is an analytical survey with a case-control time approach. The population was all medical record documents of cesarean section at RSIA Srikandi IBI Jember and the study sample was 54 documents. The sample collection technique used systematic random sampling and data collection is done by giving a checklist sheet. Data analysis using the chi-square test, and logistic regression test. The results showed that there was a relationship between age (p = 0.020), premature rupture of membranes (p = 0.016), history of ss (p = 0.005) and no relationship between parity  (p = 0.205), interval delivery (p = 1.000), height (p = 0.704), anemia (p = 0.771), twin pregnancy (p = 0.245), position disorder (p = 0.730)and there is a joint age (p = 0.009; ExpB = 16.279), premature rupture of membranes (p = 0.024; ExpB = 7.290), history of ss (p = 0.002; ExpB = 18.889) with cesarean section. There is a joint influence of age, premature rupture of membranes, and history of ss on a cesarean section at the RSIA Srikandi IBI Jember. Provide information and socialization to pregnant women about the factors that cause the cesarean section.  Abstrak: Seksio Sesarea (SS) merupakan jenis persalinan abnormal yang melahirkan janin yang mampu hidup melalui abdomen dengan tindakan pembedahan obstetrik. Kejadian persalinan seksio sesarea di RSIA Srikandi IBI Jember mengalami peningkatan dari tahun 2015 sampai tahun 2017, sedangkan pada tahun 2018 mengalami penurunan tapi secara prevalensi cenderung sama dengan kejadian seksio sesarea tahun 2017 . Persentase angka seksio sesarea dari tahun 2015 sampai tahun 2018 yaitu 59,6%, 63% 65,2% dan 60%. Tujuan: menganalisis determinan kejadian   persalinan   seksio   sesarea   di   RSIA Srikandi IBI Jember. Penelitian ini merupakan survei analitik dengan pendekatan waktu case control. Populasi adalah seluruh dokumen rekam medis persalinan seksio sesarea di RSIA Srikandi IBI Jember dan sampel penelitian sebesar 54 dokumen. Teknik pengumpulan sampel menggunakan systematic random sampling dan pengumpulan data dilakukan dengan lembar checklist. Analisis data menggunakan uji chi square, dan uji regresi logistic. Hasil penelitian diketahui ada hubungan usia (p=0,020), ketuban peah dini (p=0,016), riwayat ss (p=0,005) dan tidak ada hubungan paritas (p=0,205), jarak kelahiran (p=1,000), tinggi badan (p=0,704), anemia (p=0,771), kehailan kembar (p=0,245), kelainan letak (p=0,730)  serta ada pengaruh secara bersama-sama usia ibu (p=0,009; ExpB=16,279), ketuban pecah dini (p=0,024; ExpB=7,290), riwayat ss (p=0,002; ExpB=18,889) terhadap kejadian persalinan seksio sesarea di RSIA Srikandi IBI Jember. Ada pengaruh secara bersama-sama usia ibu, ketuban pecah dini dan riwayat ss terhadap kejadian persalinan seksio sesarea di RSIA Srikandi IBI Jember. Pemberian informasi dan sosialisasi kepada ibu hamil mengenai faktor penyebab seksio seksarea.